Consider leviathan: narratives of nature and the self in job - Doak, Brian (Fortress Press, 2014)
Brian R. Doak observes that the book of Job uses metaphors drawn from the natural world, especially of plants and animals, as raw material for thinking about human suffering. Doak argues that Job should be viewed as an anthropological "ground zero" for the traumatic definition of the post-exilic human self in ancient Israel. Consider Leviathan explores the text at the intersection of anthropology, theology, and ecology, opening up new possibilities for charting the view of nature in the Hebrew Bible